RANKL Inhibition Improves Bone Properties in a Mouse Model of Osteogenesis Imperfecta - Bargman, Renee (2010)
Recently, a new class of agents targeting the receptor activator of nuclear factor-κB ligand (RANKL) pathway has been developed for the treatment of osteoporosis and other bone diseases. In the current study, inhibition of the RANKL pathway was evaluated to assess effects on “bone quality” and fracture incidence in an animal model of osteogenesis imperfect (OI), the oim/oim mouse. Juvenile oim/oim (~6 weeks old) and wildtype (+/+) mice were treated with either a RANKL inhibitor (RANK-Fc) or saline. After treatment, bone density increased significantly in the femurs of both genotypes. Femoral length decreased with RANK-Fc in +/+ mice. Geometric measurements at mid-diaphysis in the oim/oim groups showed increases in the ML periosteal and endosteal diameters and AP cortical thickness in the treated groups. Within +/+ groups, ML cortical thickness and ML femoral periosteal diameter were significantly increased with RANK-Fc. Biomechanical testing revealed increased stiffness in oim/oim and +/+ mice. Total strain was increased with treatment in the +/+ mice. Histologically, RANKL inhibition resulted in retained growth plate cartilage in both genotypes. The average number of fractures sustained by RANK-Fc-treated oim/oim mice was not significantly decreased compared to saline treated oim/oim mice. This preclinical study demonstrated that RANKL inhibition at the current dose improved density and some geometric and biomechanical properties of oim/oim bone, but it did not decrease fracture incidence. Further studies that address commencement of therapy at earlier time points are needed to determine whether this mode of therapy will be clinically useful in OI.